2022
DOI: 10.1186/s12909-022-03502-8
|View full text |Cite
|
Sign up to set email alerts
|

Person-centered care content in medicine, occupational therapy, nursing, and physiotherapy education programs

Abstract: Background Although person-centered care (PCC) ensures high-quality care for patients, studies have shown that it is unevenly applied in clinical practice. The extent to which future health care providers are currently offered education in PCC at their universities is unclear. We aimed to clarify the PCC content offered to students as a basis for their understanding by exploring the PCC content of Swedish national study programs in medicine, nursing, occupational therapy, and physiotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…The programme directors in the current study, described a process of implementation carried forward mainly through informal processes and by individuals with a specific interest in PCC. Our previous study supports a finding that implementation of PCC is driven by bottom-up processes, as in initiated by local course leaders [ 21 ]. The programme directors described how the implementation was carried forward through champions such as professors and other influential persons who were positive towards and even had a research interest in PCC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The programme directors in the current study, described a process of implementation carried forward mainly through informal processes and by individuals with a specific interest in PCC. Our previous study supports a finding that implementation of PCC is driven by bottom-up processes, as in initiated by local course leaders [ 21 ]. The programme directors described how the implementation was carried forward through champions such as professors and other influential persons who were positive towards and even had a research interest in PCC.…”
Section: Discussionsupporting
confidence: 89%
“…In Europe, higher education is driven by the Bologna process, which focuses on general national learning objectives, and freedom is given to universities and colleges to design content and implement local programme syllabuses and local course syllabuses [ 18 , 19 ]. A previous study from our group exploring the PCC content in national study programmes, found that content related to PCC (including related concepts such as patient-centred consultation or client-centred practice), was limited, a finding in line with a study from Canada [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the volume of person-centred care content varies broadly in HPE. 1 One acknowledged approach to designing curriculum that is personcentred is to embed resources that have been co-produced by patients with lived and living experience. 2,3 In this article, we aim to provide a guideline for the inclusion of asynchronous interdisciplinary video resources that have been co-produced by patients with lived and living experience.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring that health professional education (HPE) is person centred is vital in the pursuit of person‐centred clinical care. However, the volume of person‐centred care content varies broadly in HPE 1 . One acknowledged approach to designing curriculum that is person‐centred is to embed resources that have been co‐produced by patients with lived and living experience 2,3 .…”
Section: Introductionmentioning
confidence: 99%